Pemodelan Perubahan Kebutuhan Pelanggan Menggunakan Case Tool - Nia SST.., M.Kom Saurina (Melek IT : Information Technology Journal, 2015)
Changing needs of a significant impact on the improvement of software development costs. Limitations of available resources to realize the need for change causes a change needs to be managed. Among the methods used to manage it is to analyze the dependencies along with weight changes and give priority to the need for change to be realized in order to optimally match the available resources. PT. Arcadia Global Media is a company engaged in the field of Field Services in the field of Media Placement Service (Indoor / Outdoor), Production of Signage, Booth & Maintenance and Design & Digital Printing. Changing needs of customers can lead to chaos on keterselesaian project. Labeled Transition System can capture the flow and changes in the transition to the changing needs. To map the changing needs and explore the impact it done modeling requirements change. This study propose a labeled trasition System (LTS) to model the changing needs. LTS is an effective model to describe the change in behavior of the system and was developed to model the changing needs of the software, making it easier for stakeholders to observe the flow changes and their impact needs. With LTS models are to provide solutions to the changing needs of the realization strategy.